2018
DOI: 10.1681/asn.2017090949
|View full text |Cite
|
Sign up to set email alerts
|

IL-17C/IL-17 Receptor E Signaling in CD4+ T Cells Promotes TH17 Cell-Driven Glomerular Inflammation

Abstract: The IL-17 cytokine family and the cognate receptors thereof have a unique role in organ-specific autoimmunity. Most studies have focused on the founding member of the IL-17 family, IL-17A, as the central mediator of diseases. Indeed, although pathogenic functions have been ascribed to IL-17A and IL-17F in the context of immune-mediated glomerular diseases, the specific functions of the other IL-17 family members in immunity and inflammatory kidney diseases is largely unknown. Here, we report that compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 41 publications
8
65
0
1
Order By: Relevance
“…We showed the proinflammatory role of IL-17C in established mouse models for lupus nephritis and crescentic glomerulonephritis. In accordance with the mentioned previous studies, our experiments showed expression of Il17re by T H 17 cells and significantly less T H 17 cells in inflamed kidneys of both Il17c −/− and Il17re −/− mice (24).…”
Section: Several T H 17-driven Autoimmune Diseases Are Exacerbated Bysupporting
confidence: 93%
See 4 more Smart Citations
“…We showed the proinflammatory role of IL-17C in established mouse models for lupus nephritis and crescentic glomerulonephritis. In accordance with the mentioned previous studies, our experiments showed expression of Il17re by T H 17 cells and significantly less T H 17 cells in inflamed kidneys of both Il17c −/− and Il17re −/− mice (24).…”
Section: Several T H 17-driven Autoimmune Diseases Are Exacerbated Bysupporting
confidence: 93%
“…Validating this finding, our group found strong Il17re expression IL-17A + YFP + cells from IL-17A YFP + fate reporter mice and in T H 17 polarized cells (compared to T H 0, T H 1, and Treg cells) (24). Similar to IL17C, we reported that Il17re was upregulated 24 h after induction of NTN (24).…”
Section: The Il-17ra/re Receptor Complex Is Expressed On Both Epithelsupporting
confidence: 62%
See 3 more Smart Citations